Kajian penggunaan Teori dan Pendekatan Space Syntax pada Perancangan Pasar - Ridafa Dini Yuliantie; Muhammad Fajri Romdhoni (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2025)
The space syntax paradigm and theory developed by Bill Hillier has commonly been used in planning and design, focusing on understanding or analysing the relationships between spaces and humans, particularly in public spaces. The specific focus of public space in this study is the market. The problem formulated for discussion is whether this concept can assist in designing the market to have good spatial accessibility and even movement patterns in each area. This research utilises a literature review method with a building design approach that incorporates the space syntax concept in planning and design to obtain relevant research findings. In several pieces of literature, the use of space syntax itself can provide insights into designing and achieving the goal of ensuring easy accessibility and good movement patterns in market spaces. Consequently, it can be concluded that space syntax can serve as a tool in design by seeking alternatives to address existing issues so that building users feel comfortable.